Preparation of Na2SiO3/CaO/KF Catalyst for Biodiesel Synthesis - Fan, Fenglan; Gao, Chengguang; Jia, Lihua; Guo, Xiangfeng (Asian Journal of Chemistry, 2013)
A nanosized Na2SiO3/CaO/KF solid base catalyst was prepared by grinding method. The characterized results showed that the new crystal KCaF3 was formed in the catalysts. Under the optimal conditions, the biodiesel yield can reach 97 %.